PRAKTIK JUAL BELI PERHIASAN EMAS DENGAN CARA TUKAR TAMBAH DITINJAU DARI HUKUM ISLAM DI KECAMATAN BANTAN - Nor Lolita Mayasari; Susilawati; Zakaria Batubara; Ridwan Harahap (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Buying and selling in Islam must be carried out in accordance with the provisions of sharia'. Most people do not know that its implementation is in accordance with Islamic law. One of the buying and selling that often occurs in society is buying and selling gold jewelry by means of exchange. Sociological/empirical legal research method with primary data coming from the community as informants and secondary data coming from written data. The data collection techniques used were interviews, documentation and observations carried out in Selatbaru Village, Bantan District, Bengkalis Regency. The subjects in this research were sellers and buyers of gold jewelry, while the object of research was the practice of buying and selling gold jewelry by means of exchange which occurred in Bantan District. Data can be analyzed qualitatively which produces descriptive data. The results of the research are the practice of buying and selling gold jewelry by exchange, there are problems in the form of exchange transactions with different grades and types of gold and non-cash payment systems. Based on research results which are linked to existing legal theory, gold jewelry buying and selling transactions by exchange in Bantan District are in line with Islamic law based on the DSN-MUI Fatwa. However, other opinions say it is not in accordance with Islamic law.